DINAMIKA PENDIDIKAN PEREMPUAN DALAM SEJARAH ISLAM - Takunas, Rusli (Pusat Studi Gender dan Anak, IAIN Palu, 2018)
This paper discusses the Dynamics of Women's Education in Islamic History. In tracing the history books, the work of Islamic historians relating to women's education in general in the Islamic world and in Indonesia since the classical era, setbacks, reforms, found the dynamics and variations of public appreciation of educational opportunities for women. In some historical periods, women are considered second-class citizens, so they do not have access to education and self-development that is equal to men. While in the view of Islam men and women have the same position. This study concludes that in the history of Islam in a period of decline, women were not only restricted in attending education but they were marginalized and prohibited from participating in social activities. In the classical and renewal period, women and men have the same position in terms of education and social activities.